The Accessibility Levels of the Websites of Federal Higher Education Institutions in Northeast Brazil - Santos, Luana Lobo dos; Ferreira, Ramon Maciel; Rangel, Thayron Rodrigues (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie)

(untitled) (Canadian Association for Information Science - Association canadienne des sciences de l'information, 2024)
The general aim of this study is to make a diagnosis on the accessibility of information made available on the websites of the Federal Higher Education Institutions (IFES) in the Northeast. It is based on the hypothesis that the websites of the IFES in the Northeast Region of Brazil do not have high levels of adequacy, results that do not allow any user, regardless of being a person with disabilities or other limitations, to access the knowledge made available there, either with the help of assistive technologies or autonomously. The methodological procedures will be bibliographical and documentary research with analysis of primary sources on institutional websites and administrative acts made available, or not, on these sources. All the open data portals will be evaluated and simulated to determine their suitability for eMAG. This will be done using the public software ASES, a system for comparing and validating the standards of construction and behaviour of the source code of electronic sites, pointing out the levels of usability, navigability, alternative text, and content markers regarding the eMAG parameters, which are mandatory for public institutional sites in Brazil in terms of digital accessibility. As a result of the research, it was possible to identify that the levels of accessibility on the websites of these institutions were not in line with the parameters of the Digital Government Accessibility Model (eMag) of Brazil. This reveals divergences in the promotion of access to information; while some IFES make information available autonomously, without facing noise, interference, or impediments to the use of information, others do not so much, which has a negative impact on the guarantee of rights such as the exercise of full citizenship.